1988
DOI: 10.1073/pnas.85.18.6836
|View full text |Cite|
|
Sign up to set email alerts
|

Organization of the human alpha 2-plasmin inhibitor gene.

Abstract: We have isolated overlapping phage genomic clones covering an area of 26 kilobases that encodes the human alpha 2-plasmin inhibitor. The alpha 2-plasmin inhibitor gene contains 10 exons and 9 introns distributed over approximately 16 kilobases of DNA. To our knowledge, the number of introns is the highest yet reported for a member of the serine protease inhibitor (serpin) superfamily. All introns are located in the 5'-half of the corresponding mRNA. The 5'-untranslated region and the leader sequence are interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…10,[36][37][38][39][40] The gene contains 10 exons and 9 introns and spans approximately 16 kb of DNA. 41 The complete complementary DNA sequence shows 23% to 28% homology with other members of the serpin family and 73% to 81% homology with a2AP from other species, such as rat, mouse, cow, and rabbit. 42,43 Exon 1 of the human SERPINF2 gene consists entirely of untranslated sequences.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10,[36][37][38][39][40] The gene contains 10 exons and 9 introns and spans approximately 16 kb of DNA. 41 The complete complementary DNA sequence shows 23% to 28% homology with other members of the serpin family and 73% to 81% homology with a2AP from other species, such as rat, mouse, cow, and rabbit. 42,43 Exon 1 of the human SERPINF2 gene consists entirely of untranslated sequences.…”
mentioning
confidence: 99%
“…The amino terminal (N-terminal) region of the protein comprising the glutamine involved in crosslinking to fibrin is encoded by exon 4, whereas both the RCL containing the reactive site arginine and the plasminogen-binding site in the C-terminal region are encoded by exon 10. 41 An alternatively spliced isoform of a2AP has been reported that lacks exon 5 (NM_001165921), although the expressed amount of this variant or any consequences of its function have not yet been described.Native a2AP molecules contain 11% to 14% carbohydrate (four putative N-linked glycosylation sites at asparagine residues 99, 268, 282, and 289) and a sulfated tyrosine residue at position 457.44 This leads to a molecular weight of approximately 67 000. 10,14,36 Furthermore, a2AP contains 1 disulfide bridge (between the cysteine residues in positions 43 and 116) that does not appear to have a profound influence on the structure or function of a2AP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agarose gel electrophoresis, transfer to nitrocellulose filters, hybridization, washing of filters and autoradiography were carried out by standard procedures (18). For use as probes, a 750 base pair (bp) Eco RI/Hind III fragment of the human a2PI cDNA clone pPI39 (11), coding for the carboxyl-terminal half of a2PI, and an 890 bp Pst I fragment of the human genomic a2PI clone XPI6 (15), containing exons II, III, and IV, were labeled with a_-[32P]dCTP by nick translation.…”
Section: Methodsmentioning
confidence: 99%
“…However, nothing was known about the molecular basis for the patients with congenital a2PI deficiency with no detectable circulating antigen. Since we have isolated and characterized the human a2PI gene (15), it has now become possible to analyze the gene from these patients with a2PI deficiency. Therefore, this study was undertaken to elucidate the molecular basis for a pedigree of hereditary a2PI deficiency by analyzing the a2PI gene from an individual homozygous for this trait (16).…”
mentioning
confidence: 99%